PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIRS SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 01 SEJANGAT KEC. BUKIT BATU - Zauni Kartini; Lazim N Lazim N; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This examination is able to increase the result of IPA lesson with applying cooperative lesson type of Think Pairs Share (TPS) to an elementary school of grade III, SDN 1 Sejangat, Bukit Batu districk, Bengkalis residence. This examination helds from 3 March till 25 March 2015 – subject of thisexamination is elementary student grade 3 SDN 1. Comprehendea by 17 boys and 13 girls, from this examination, we can conelude that the aapplication of cooperative lesson type of TPS can increase the result of IPA lesson to elementary student grade 3 SDN 1 Sejangat, Bukit Batu distric. We can know that from : 1) Increasing the activity of teacher`s meeting percentage where the first siklus activity of teacher`s meeting percentage just 53,57%, in 2nd meeting, increase to be 67,86%, had increasea 14,29%. Then teacher`s activity in 2nd meeting had increased 75,00%, is increased to be 7,14%, and in 4th meeting, teacher`s activity increased to be 92,86% increased 17,86%. Activity of student`s meeting percentage increased when a fist siklus first meeting, activity of student percentage just 46,43% and in 2nd meeting, increased to be 60,71%, increased to be 14,29%. Then in 2nd siklus, 3nd meeting, activity of student percentage increased to be 82,14%, increased 21,43%, and in 4nd meeting to be 92,86%, and increased 10,71%. 2) The result of student`s lesson individu from basic score to 2nd siklus had increased, where in the basic score, the average of student`s lesson result 70,50% in frist siklus increased to be 71,50. With increased 1.00 point or 1,42%. In 2nd siklus, average of student leeson result 87,33% with inchresed 15,83 point or 22,14%. 3) Student`s lesson result in clasical we or basic score is 36,67%, in first siklus increased to be 46,67%, increased to be 27,27% and in 2nd siklus increased to be 93,33 incrased to be 99,98%.Keywords : Cooperative Learning Type Think Pairs Share, increasing IPA